knowledge and attitude of Iraqi women in reproductive age group about risk factors in pregnancy - Thamer Yahyaa, Badeaa; Ali Altaha, Mahasin; Abdulhadi Al-Rawi, Ru’ya; Ali Mustafa Al-Samarrai, Mustafa; Ali Jadoo, Saad Ahmed (Journal of Ideas in Health, 2022)
Improved knowledge among women about maternal risk factors significantly reduced the likelihood of adverse events in pregnancy and childbirth. This study aimed to explore Iraqi women's knowledge and attitudes about maternal risk factors in pregnancy. A multicenter cross-sectional survey was conducted from 01 January to 31 March 2019 among women of the reproductive age (15-49 years). A convenient sampling technique using a semi-structured questionnaire was recruited to interview the sample. SPSS version 16.0 was used to analyze the data. Descriptive and inferential statistics (Chi-square test) were used to present data with the significance level considered at <0.05. Data of 250 women underwent final analysis. The mean age of respondents was 27.76 (±6.3 years). Most of the respondents (79.9%) correctly knew the maternal risk factors in pregnancy. A large percentage of women knew that poor nutrition, anemia (95.6%), smoking and passive smoke (95.6%), and obesity (85.2%) during pregnancy are risk factors affecting the fetus’ health. However, about 40.0% of women thought there was no harm during pregnancy, and therefore there was no need for medical check-ups regularly. In bivariate analysis, there was a significant association between knowledge and level of education. The higher the level of education, the greater the women's knowledge about risk factors such as malnutrition and anemia (P=<0.001), obesity (P=0.04), diabetes (P=0.002), repeated urinary tract infection (P=0.017), Rh incompatibility (<0.001), history of previous cesarean section (P=0.010), smoking and passive smoking (P=0.014) and evidence of bleeding (P=0.001). In conclusion, Iraqi pregnant women demonstrated a good level of knowledge about the risk factors during the pregnancy.